Amduat und Klassisches Himmelsbild (zu Amduat 325–328, 396–399 und 757–758) - Lieven, Alexandra von (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
In the Fourth Hour of the Great Amduat, the group of deities 325 to 328 are identified as forms of Orion, Sothis and the planet Venus in disguise. This leads to some general observations on Venus and to a lesser extent Mercury within Egyptian Religious Astronomy. As the scene in question is one of only three that is made up of complete figures in red ink in the version of Thutmosis III, it is investigated what might link these three scenes. Ultimately, a possible connection to issues of time measurement is proposed. Another one of these three scenes in red ink is in the Fifth Hour. It concerns figures 396 to 399 holding four crowns on their knees. This scene provides some ties with conceptions prominent for example in Edfu. The four crowns together form the -crown often attested for Horus of Edfu. As the astral form of this god is Venus, the Fourth and Fifth Hours prove to be closely bonded.